PENGARUH PROGRAM PEMUTIHAN DENDA PAJAK KENDARAAN BERMOTOR, PEMBEBASAN BEA BALIK NAMA KENDARAAN BERMOTOR, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA UPT SAMSAT KOTA AMBON (Studi Empiris Pada Mahasiswa FEBIS Universitas Pattimura Ambon) - Fresilya Claudya Rameltha Tatuhey; Linda Grace Loupatty , Trisna Sary Lewaru (CV. Adiba Aisha Amira, 2024)
This study aims to test whether the amnesty of motor vehicle tax fines, exemption of motor vehicle transfer fees, and quality of service aflect the compliance of motor vehicle taxpayers. The independent variables in this study are the tax fine amnesty program, exemption of transfer fees, quality of service, while the dependent variable is the compliance of motor vehicle taxpayers. This study was conducted at the UPT Samsat Ambon City. This study is a quantitative study using primary data and a sample of 100 respondents. The data collection technique uses a survey technique using a questionnaire. Data analysis uses multiple linear regression statistical analysis. The results of the study indicate that the amnesty of motor vehicle tax fines and exemption of motor vehicle transfer fees have no eflect on taxpayer compliance, and the quality of service has a positive and significant eflect on taxpayer compliance